A bonding evolution theory study of the reaction between methylidyne radical, CH(X2Π), and cyclopentadiene, C5H6. Issue 11 (1st February 2022) - Andrés, Juan; Safont, Vicent S.; Oliva, Mónica; Caster, Kacee L.; Goulay, Fabien
Abstract: In the present work, bonding evolution theory (BET) is applied to gain insight about the complex reaction between methylidyne radical, CH (X 2 Π) and cyclopentadiene, C5 H6 . The novelty of this work is that all reaction pathways take place in the doublet electronic state and an unpaired electron is always present. Therefore, taking the aforementioned reaction as explicative example, we have shown how to apply the BET tool to these kinds of open‐shell systems, by splitting the wavefunctions into the corresponding alpha and beta parts. As an added value, we have included a point‐by‐point description of the algorithm we use to make it available for the readers. Hence, a complete analysis of bond breaking/forming and charge redistribution along the multi‐channels connecting reactants to products via the transition states and intermediates is presented. We show how the BET brings about the representation of the electronic flow in complex molecular rearrangements like the one herein studied, yielding a transparent rationalization based on the electron density redistribution. The present study allows us to conclude that along the different processes giving rise to the benzene product, the breaking of a CC sigma bond initiates the electronic rearrangement in two cases, but not in the third one. The last step in these processes can be described as an initial weakening of the CH bond with a quasi‐hydride formation and a final retro‐transfer of electrons from the quasi‐hydride to the CH bond. On the other hand, in the way to the fulvene product, the breaking of the CC sigma bond takes place after previous electronic redistribution. Neither the last step of the fulvene formation process nor the interesting H transfer described in the second one, can be explained without the wavefunction splitting technique herein detailed and exemplified. Abstract : Bonding evolution theory characterization of a complex reaction mechanism taking place in an open‐shell system.